Determination of the Recreational Landscape Potential of Tarsus (Mersin) District and Its Surroundings for Tourism - Elif Akpınar Külekçi; Sümeyye Gencer (Journal of Architectural Sciences and Applications, 2023)
The study conducted an investigation into the effective utilization of Tarsus district's historical and cultural assets in Mersin province, with a focus on its tourism potential. The primary objectives were to promote the region and contribute to its economic, social, and cultural advancement. A survey was administered to gather information on dominant tourism types in Tarsus, including historical sites, cultural landmarks, local crafts, cuisine, caves, camping, wildlife, flora, gastronomy, local resources, natural attractions, and aesthetics. The results highlighted Tarsus' prominence due to its cultural heritage, historical structures, and natural wealth. Despite Tarsus's cultural diversity and tourism potential, the study revealed its current underrepresentation and various challenges, including the vulnerability of historical assets, insufficient infrastructure, and unguided utilization. The study suggests adopting a sustainable approach that balances conservation with utilization to address these issues and help Tarsus attain the recognition it rightfully deserves in the field of recreation and tourism.